Eksploitasi Tubuh Perempuan di Televisi Sebagai Ironi Kepribadian Indonesia - BANIN DIAR SUKMONO (Komunikator, 2012)
This discussion aims to see how exploitation has happened towards women through and by the media in the 21st century, which is controlled by the capitalists, and its relationship with the 2nd sila (principle) of Pancasila. This discussion tries to analyze by observing the figure of “cewek kece” (hot chicks) as the ideal female figure in the 21st century on television. The results of the analysis proved that the exploitation of women’s bodies has happened through and by the media, especially television. It is in the form of commodification of “cewek kece”, symbolic violence, and the pressure towards women to have slim bodies. For the results of this analysis, when it is associated with the 2nd sila of Pancasila, it indicates that there is an incompatibility between the exploitation of women’s bodies and the values and teachings of Pancasila as the foundation of national identity. Keywords: cewe kece, exploitation, commodification, the 2nd sila of Pancasila